The effects of in utero HIV and ART exposure on infant T-cell and monocyte activation, function and regulation of immune-modulatory pathways - Rossouw, Theresa M. (University of Pretoria, 2024)
Thesis (PhD (Medical Immunology))--University of Pretoria 2024.